DATA VISUALISASI TINGKAT KENAIKAN LIMBAH SAMPAH DI INDONESIA - Madyatmadja, Evaristus Didik; Widjaja, Samuel Axel; Haryo Pangukir, Joseph Priadi; Budiharjo, Matthew; Rianky, Rianky; Heryanda, Oktavian (ISTEK WIDURI, 2023)
Waste or garbage is a leftover material that has no use or is disposed of after daily activities by humans. The purpose of this research is to know whether waste in Indonesia has increased or not in the last three years and to find out what type of waste is the most in the last three years, and finally, what province has the largest pile of waste in the last three years. This research uses the method that has some procedures. They are acquired, parse, filter, mine, represent, refine, and interact. The visualization data used is using Microsoft Excel. There are two pieces of data, data on waste generation per year and data on the most types of waste from 2020 to 2022 in Indonesia based on SIPSN data. Data from SIPSN already in Microsoft Excel is inserted into Power BI by selecting